Interdisciplinary approach of Yalom's group therapy factors: A theoretical model for including animal presence in social work education and practice - Rusu, Alina Simona; Davis, Rebecca (Frontiers in Veterinary Science, 2022)
An increasing number of studies in the field of Social Work (SW) address the incorporation of animal presence in practice and improved understanding of social support and therapeutic components. Education programs on the ethical and practical principles of animal-assisted interventions, including models and theories supporting the psycho-physiological effects of human-animal interactions (HAI), are being implemented around the world, especially in the US. While designing and implementing a new interdisciplinary curriculum can be time-consuming and, depending on the many variables, integrating elements of HAI components in existing curricula can be a more efficient approach. We present a step-by-step approach for inclusion of HAI knowledge and practice in teaching Yalom’s principles and therapeutic factors of group therapy to SW students. Based on a qualitative analysis of the existent literature and on the results of several research projects in the field of HAI, we propose an approach for infusing research-informed examples and theories supporting the beneficial effects of HAI in the direction of the interdisciplinary understanding of the Yalom’s primary factors in the therapeutic process, such as: instillation of hope, corrective recapitulation of the primary family group, development of socializing techniques, imitative behavior, interpersonal learning, and group cohesion. Applied values of HAI are discussed for each factor, emphasizing the added value of animal presence in group therapy settings from the perspective of the dynamic of interspecific social networks, i.e. animal-handler-group members.